2011
DOI: 10.1007/s10534-011-9435-4
|View full text |Cite
|
Sign up to set email alerts
|

Uranium, thorium and rare earth elements in macrofungi: what are the genuine concentrations?

Abstract: Concentrations of uranium, thorium and rare earth elements (REE) in 36 species of ectomycorrhizal (26 samples) and saprobic (25 samples) macrofungi from unpolluted sites with differing bedrock geochemistry were analyzed by inductively coupled plasma mass spectrometry (ICP-MS). Analytical results are supported by use of certified reference materials (BCR-670, BCR-667, NIST-1575a) and the reliability of the determination of uranium was verified by epithermal neutron activation analysis (ENAA). It appears that da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 24 publications
5
46
2
Order By: Relevance
“…Particularly notable are the results of Borovička et al [23], who give concentrations for some heavy metals several orders of magnitude lower than those found in our analysis [24,25]. It must be noticed that, although the spectrometer was thoroughly calibrated, it seems that the methodology of X-ray fluorescence may not be adequate when the concentrations are close to the low detection limit (e.g., heavy metals).…”
Section: Resultscontrasting
confidence: 72%
“…Particularly notable are the results of Borovička et al [23], who give concentrations for some heavy metals several orders of magnitude lower than those found in our analysis [24,25]. It must be noticed that, although the spectrometer was thoroughly calibrated, it seems that the methodology of X-ray fluorescence may not be adequate when the concentrations are close to the low detection limit (e.g., heavy metals).…”
Section: Resultscontrasting
confidence: 72%
“…For uranium we use of the most intensive 106 keV peak of 239 Np. The degree of interference strongly depends on the detector resolution and on the way of activation (El-Taher, 2010d;El-Taher, 2010e;Borovička et al, 2011;Zhao et al, 2008;Suzuki et al, 2010). Table 5 summarizes the nuclear data and the average concentrations of fifteen elements determined in natural quartz samples in mg/kg or percent compared with Turekian models of geochemical distribution of elements in the earth crust (Turekian, 1971;Turekian and Wedepohl 1961).…”
Section: Resultsmentioning
confidence: 99%
“…The fruit bodies of P. ostreatus and P. pulmonarius strains were collected from 19 mushroom farms. The tested fruit bodies were obtained from each mushroom grower in several cultivation cycles each year Bernaś et al 2006;Maihara et al 2008;Muñoz et al 2005;Kalač 2010;Costa-Silva et al 2011;Zhu et al 2011) b P. florida (Alam et al 2008;Mallikarjuna et al 2013) c P. djamor (Rodriguez Estrada andRoyse 2007, Guo et al 2007;Lee et al 2009, Mallikarjuna et al 2013 d P. citrinopileatus (Rodrigues et al 2015) e P. eryngii (Rodriguez Estrada andRoyse 2007, Akyüz andKirbağ 2010;Zhu et al 2011) f P. pulmonarius (Oliveira Silva et al 2002;Vetter 2003, 2005, Borovicka et al 2011 in the period 2009-2015. The weight of a single fruit body sample amounted to 1 kg.…”
Section: Experimental Materialsmentioning
confidence: 99%
“…However, no maximum permitted levels have yet been set for inorganic As and methylmercury, although they are the most toxic species of As and Hg, respectively (Cordeiro et al 2015). The research of Borovicka et al (2011) showed that P. pulmonarius collected from unpolluted sites in the Czech Republic contained trace elements such as U and Th at levels of 3.25 and 11.4 μg kg −1 dm, respectively; Ag and Pb at 7.55 and 0.13 mg kg −1 dm, respectively. A study undertaken by Vetter (2005) showed Li content in P. pulmonarius to be 0.063-0.077 mg kg −1 dm.…”
Section: Introductionmentioning
confidence: 99%